John Sevier correspondence - Sevier, John, 1745-1815.
Clerk's copy of a letter (1797 January 12) from Sevier, governor of Tennessee, to Silas Dinsmore, Indian agent, relating to Tennessee boundaries and to the Cherokee Indians; and ALS (1812 May 31) from Sevier to his son, George Washington Sevier, concerning the impending war with Great Britain and British alliances with the Cherokee, Chickasaw, and Creek Indians.
Army officer, U.S. representative from North Carolina and Tennessee, and governor of Tennessee.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Dinsmore, Silas -- Correspondence; Sevier, George Washington -- Correspondence; Cherokee Indians; Chickasaw Indians; Creek Indians; Indians of North America -- Government relations -- 1789-1869.; Indians of North America -- Government relations -- Great Britain; Tennessee -- Boundaries; United States -- History -- War of 1812.; Army officers; Governors -- Tennessee; Representatives, U.S. Congress -- North Carolina; Representatives, U.S. Congress -- Tennessee